Modern Basics Philosophy of Education - Oleg Bazaluk; Tamara Blazhevych (International Society of Philosophy and Cosmology, 2015)
In thisarticle the authors examine the current understanding ofthe foundations ofthe philosophy of education. Lately when it is spoken about human development and education and concretized that it is the perfection of its mind. And if at the end of the twentieth century the subject of educational impact was human being, consisting of social and biological entities, at the beginning of the XXI century the situation has changed. Advances in neuroscience (Risto Nааtаnеn, James Olds, Donald Hebb, Elkhonon Goldberg and others) allowed specifying the subject of the educational impact and identifying in a person the material organization that really makes him standing out from the world of living organisms. We are talking about the neural structures that are formed and developed in the human brain and which are not observed (and if they are observed, then in a different format and with different functional manifestations) in the brain of higher animals. We are talking about consistently evolving neural networks and subconscious consciousness which perform the corresponding functions: subliminal (unconscious) and conscious. If the consistent development of the structure of the human brain sees neuroscience, the development of the functions of this structure, considering psychology. Methods, ways and means of transmission of socio-cultural heritage from one generation to another explores pedagogy. Therefore, the philosophy of education that considers the impact of educational technology, global educational model should be based on the integration of research in neuroscience, psychology and pedagogy.